Synthesis and characterisation of PEGDA-based hydrogels crosslinked with pentaerythritol tetrakis (3-Mercaptopropionate) - Toh, Jia Ban. (2011)
PEGDA-based hydrogels have been synthesised successfully by photopolymerisation and Michael-type addition reaction. Before the hydrogel is prepared, degree of acrylation is determined by 1H NMR characterisation. Photo-crosslinked hydrogels has been characterised by FTIR and show successful thiol-linkage with the acrylate moieties. Selected PEGDA-based hydrogels have been put through Instron tensile and cyclic tests, and show highly elastic behaviour. The rheometry test reaffirmed the high elastic behaviour of selected PEGDA-based hydrogels through its corresponding high storage moduli for PEGDA macromers synthesized from PEG of Mw 8000 Da and 10000 Da. Equilibrium swelling test indicates the high water content and swelling ratio of photo-crosslinked hydrogels synthesized with PEGDA macromers with high degree of acrylation. Similar trend is found in Michael-type addition crosslinked hydrogels synthesized from PEG of Mw 4000 Da, 8000 Da and 10000 Da.